1974
DOI: 10.1038/bjc.1974.188
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Glucose on the Development of Experimental Metastases

Abstract: Summary.-The effect of 10% glucose solution and narcosis upon the blood borne cancer cells was studied on Wistar rats, with Walker 256 carcinosarcoma inoculated intravenously.Our experiment reveals obvious differences between the control group and the groups treated with glucose concerning incidence, localization and tumour extension, differences which suggest that there is a risk in using glucose in the intra-and post-surgical resuscitation of patients with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
1982
1982

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…A study of rats inoculated intravenously with Walker 256 carcinosarcoma cells found a marked increase in tumor incidence in those whose inoculation was preceded by intravenous glucose infusion. 8 This was attributed to insulin activation of DNA polymerase and a resultant increase in DNA synthesis and cell proliferation. The fact that rats fed a glucose solution tend to drink greater volumes than those given water has been determined in a concurrent study, and the effect of this increased fluid intake on tumor development is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A study of rats inoculated intravenously with Walker 256 carcinosarcoma cells found a marked increase in tumor incidence in those whose inoculation was preceded by intravenous glucose infusion. 8 This was attributed to insulin activation of DNA polymerase and a resultant increase in DNA synthesis and cell proliferation. The fact that rats fed a glucose solution tend to drink greater volumes than those given water has been determined in a concurrent study, and the effect of this increased fluid intake on tumor development is unknown.…”
Section: Discussionmentioning
confidence: 99%